Efektifitas Sistem Pemasaran Tradisional Wisata Tradisional Berbasis Local Wisdom dan Tradisi Agama di Kabupaten Banyuwangi. - Biati, Lilit (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Alas Purwo National Park is one of the tourist attractions in Banyuwangi, which is the center of attention, especially for performers of rituals and praying for Hindus. The kawitan site is a ancestral temple which is still actively used for prayer, while many rituals are carried out in caves and on the shores of the pancur. The objectives of this study are to describe the effectiveness of traditional marketing systems based on local wisdom and religious traditions and to examine the role of local communities in promoting tourism destinations and religious traditions in Banyuwangi Regency. The research method used in this research is a qualitative research with a case study design, with an ethnographic approach, and participatory. The location of the research object is Alas Purwo National Park, Banyuwangi Regency. Data collection techniques used in-depth interviews (indept interviews), role observations (Participant Observation), and documentation (Documentation). Meanwhile, the data analysis technique used is data reduction, data display, withdrawal and data testing (drowing and ferrivying conclusions).